Cholesterol target value attainment and lipid-lowering therapy in patients with stable or acute coronary heart disease: Results from the Dyslipidemia International Study II. (November 2017) - Gitt, Anselm K.; Lautsch, Dominik; Ferrières, Jean; De Ferrari, Gaetano M.; Vyas, Ami; Baxter, Carl A.; Bash, Lori D.; Ashton, Veronica; Horack, Martin; Almahmeed, Wael; Chiang, Fu-Tien; Poh, Kian Keong; et al.
Abstract: Background and aims: Low-density lipoprotein cholesterol (LDL-C) is a major contributor to cardiovascular disease. In the Dyslipidemia International Study II (DYSIS II), we determined LDL-C target value attainment, use of lipid-lowering therapy (LLT), and cardiovascular outcomes in patients with stable coronary heart disease (CHD) and those suffering from an acute coronary syndrome (ACS). Methods: DYSIS II included patients from 18 countries. Patients with either stable CHD or an ACS were enrolled if they were ≥18 years old and had a full lipid profile available. Data were collected at a physician visit (CHD cohort) or at hospital admission and 120 days later (ACS cohort). Results: A total of 10, 661 patients were enrolled, 6794 with stable CHD and 3867 with an ACS. Mean LDL-C levels were low at 88 mg/dl and 108 mg/dl for the CHD and ACS cohorts respectively, with only 29.4% and 18.9% displaying a level below 70 mg/dl. LLT was utilized by 93.8% of the CHD cohort, with a mean daily statin dosage of 25 ± 18 mg. The proportion of the ACS cohort treated with LLT rose from 65.2% at admission to 95.6% at follow-up. LLT-treated patients, who were female, obese, or current smokers, were less likely to achieve an LDL-C level of <70 mg/dl, while those with type 2 diabetes, chronic kidney disease, or those taking a higher statin dosage were more likely. Conclusions: Few of these very high-risk patients achieved the LDL-C target, indicating huge potential for improving cardiovascular outcome by use of more intensive LLT. Highlights: LDL-C target attainment extremely low for very high-risk CHD and ACS patients. Statin dosages not maximized, with scarce use of combination therapies. Under-treatment of hyperlipidemia on a global scale.